Soil formation - Scott, Robert Douglas (My University, 1904)
Introduction: Soil is defined as disintegrated and pulverized rock, mixed with animal and vegetable matter, the proportions of each being variable, ranging from a trace to quite a large percentage of either constituent. The rock particles are of different kinds and. sizes, and are in different stages of disintegration. The kind of rock disintegrated influences the character of the soil formed both chemically and physically; the former from the minerals it contains, the latter from the size of particles it yields, and other physical phenomena. Consequently we have on the one hand "sandstone", "limestone", "alkali" and soils of like nature, on the other, based upon the fineness of the particles, "sand", "silt", "loam" and "clay" soils, and various modifications of each. Soils are also divided as to relative position. The upper portion, in humid regions from six to twelve inches, is known as "soil", while that below is "subsoil". Soil and subsoil may be widely different in character, both chemically and physically, or they may be identical. In humid regions the subsoil is often found unproductive and of a different color from the soil. In arid regions these differences disappear. The difference in subsoils, as well as in soils, of humid and arid regions is probably…
Citation: Scott, Robert Douglas. Soil formation. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Soil Formation; Soils; Geology; Soil Composition; Theses